Over a million students use our free study notes to help them with their homework
Recognise that the form this question is a circleRemember alternate circle equation (x + a)2 + (x + b)2 = r2Where centre of circle (-a,-b) and r is the radiusTo get the ri...
Use the chain rule as this is a composite function. Let u=2x+5.So the original equation becomes y=(u)^2.Using the chain rule: dy/dx = dy/du * du/dxdy/du = 2udu/dx = 2So dy/dx= 4uSince u=2x+5, dy/dx = 4(2x...
Rearranging gives:4cos(x)-1 = 2sin(x)tan(x) Substituting in tan(x)=sin(x)/cos(x) gives:4cos(x)-1 = 2sin(x)(sin(x)/cos(x))2sin2(x)=4cos2(x)-4cos(x)Substituting in 2sin2<...
Given a circle in the general form you can complete the square to change it into the standard form.x2 + 2gx + y2 +2fy +c = 0 (1). General form of an equation which has the completing...
a) Integrate ln(x) by parts: u = ln(x), dv/dx = 1, du/dx = 1/x, v = x int(udv/dx) = uv - int(du/dx * v) = ln(x)/x - x so int(ln(x) + 1/x - x) = ln(x)/x - x + ln(x) + x^2 + Cb) y = ln(x)/x - x + l...
←
83
84
85
86
87
→
Internet Safety
Payment Security
Cyber
Essentials